Faktor-Faktor yang Mempengaruhi Pertimbangan Tingkat Materialitas Audit (Studi Empiris KAP di Wilayah DKI Jakarta) - Ahmad Rafiq Anshari; Trinandari Prasetyo Nugrahanti (Universitas Kristen Maranatha, 2021)
Abstract This study aims to empirically examine the effect of auditor professionalism, auditor experience and professional ethics on the consideration of the materiality level of financial statement audits. This research method uses a causal descriptive method and the primary data source is obtained by distributing questionnaires to auditors at public accounting firm (KAP) located in DKI Jakarta area using convenience sampling technique. Data analysis was performed using multiple linear regression method and hypothesis testing using SPSS ver.23 program. The results of this study indicate that auditor professionalism, auditor experience and professional ethics have a positive effect on the consideration of the level of audit materiality in financial statements. Auditors in improving a high professionalism attitude must have a lot of audit experience so that it will be appropriate to determine the determination of the materiality level of the financial statements. In carrying out an audit of financial statements, the auditor cannot provide absolute assurance to clients or other users of financial statements that the audited financial statements are free from material misstatement. Keywords :Auditor Professionalism, Auditor Experience, Professional Ethics, and Materiality Levels